Risk Factors of Chronic Diarrhea in HIV-Infected Children - Satrio W. Fathurrahman; Pramita Gayatri (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2022)
Background. Chronic diarrhea increases mortality and other long-term morbidities in children. HIV-infected children are at higher risk of developing chronic diarrhea. Objective. This study aimed to investigate the characteristics, prevalence, and risk factors of chronic diarrhea in HIV-infected children. Methods. Data were obtained retrospectively from medical records of HIV-infected children at Dr. Cipto Mangunkusumo General Hospital (RSCM) from January 2014 until December 2016. The risk factors evaluated included age, nutritional status, dehydration status, HIV-infection phase, use of antiretroviral (ARV) drugs, and stool culture. All data that fulfilled the inclusion criteria were analyzed by bivariate followed by multivariate analysis, except for stool culture. Results. The prevalence of chronic diarrhea in HIV-infected children in RSCM was 12.98%. Analysis of 132 data showed that chronic diarrhea was significantly associated with low nutritional status (p=0.037; adjusted OR=5.737) and dehydration (p=0.026; adjusted OR=6.891) among HIV-infected children. Conclusion. Dehydration status and malnutrition are important risk factors for chronic diarrhea in HIV-infected children. These findings may also support that in managing HIV-infected children with diarrhea, one should first overcome dehydration and manage malnutrition to prevent the vicious circle of diarrhea – malnutrition – diarrhea.